Bathymetric map of Lake Peters, Alaska, 2015 - Erik Shiefer; Nicholas McKay (Arctic Data Center, 2019)
Bathymetric data were collected using a Lowrance Elite-5 HDI Combo sonar depth recorder along several transects throughout Lake Peters in August 2015. These data were used to create a bathymetric map using ArcGIS 9.1.